Self-esteem, emotional regulation, and their relationship with the risk of self-harm and physical and emotional well-being in adolescents - Fernández, Irene (2024)
Adolescence represents a crucial stage during which individuals face multiple risks that will influence their health and identity (Espinoza, 2022). Low self-esteem and emotional regulation, body dissatisfaction, and life dissatisfaction increase the risk of eating disorders and self-harm (Tigasi y Hernández, 2023). The aim is to determine the role of emotional variables in the risk of selfharm, body dissatisfaction, and life satisfaction in adolescents. Method. 86 students in the third year of Secondary Education were assessed using the following instruments: “Rosenberg Self-Esteem Scale”, “Self-Harm Risk Questionnaire (CRA)”, “Questionnaire of Influences on Body Aesthetic Model (CIMEC-26)”, “Emotional Regulation Questionnaire for Children and Adolescents (ERQ-CA)”, and “Satisfaction with Life Scale (SWLS)”. Results. A negative relationship was found between self-esteem and body dissatisfaction, as well as self-harm risk. Additionally, a positive relationship between self-esteem and life satisfaction, but not with emotional regulation. Moreover, significant gender differences were observed in all variables, except for emotional regulation. Conclusions. Fostering self-esteem is crucial for addressing body dissatisfaction and preventing self-harm. Investigating emotional variables in adolescence isessential for preventing self-harm and reducing the risk of suicide.